Molecular characterization of toxic benthic dinoflagellate, Prorocentrum lima in west Indonesian waters using LSU 28S rDNA gene - RIANI WIDIARTI; NEVIATY PUTRI ZAMANI; DIETRIECH GEOFFREY BENGEN; HAWIS MADDUPPA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Widiarti R, Zamani NP, Bengen DG, Madduppa H. 2022. Molecular characterization of toxic benthic dinoflagellate, Prorocentrum lima in west Indonesian waters using LSU 28S rDNA gene. Biodiversitas 23: 3257-3263. Prorocentrum lima is one of the toxic benthic dinoflagellates known to cause Diarrhetic Shellfish Poisoning (DSP), which is also associated with ciguatoxin-producing species, Gambierdiscus toxicus that causes Ciguatera Fish Poisoning (CFP). P. lima has a wide range of morphological variability and genetic diversity, but such research has never been reported from Indonesian waters yet. This study aimed to determine the molecular characteristics of P. limain west Indonesian waters, namely Bintan Island, Belitung Island, Seribu Islands, and Karimunjawa Islands. Molecular characterization was conducted by amplification on large subunit (LSU)28S rDNA gene. Extraction was conducted using freeze-thaw which was continued with single cell PCR method. Genetic distance values and phylogenetic analysis were analyzed using MEGA software. Based on molecular analysis, P. lima from this research was divided into two subclades, namely subclade A from Seribu Islands and Belitung Island, and subclade B from Karimunjawa Islands and Bintan Island. P. lima from Bintan Island showed a closer relationship with the reference sequence from the Genbank. Observation of molecular characters of P. lima showed that the genetic diversity of P. lima depended on the variation of the island’s morphogenesis type.These findings could support a further study on the distribution of P. lima in Indonesian waters, related to the genetic variation and toxin production, since Indonesia consists of many small islands.